Status Kepemilikan Emas Virtual di Aplikasi Shopee Perspektif Fatwa DSN-MUI Tentang Jual Beli Emas Secara Tidak Tunai - Rahma, Mevianti Nur; Hanifuddin, Iza (Invest Journal of Sharia & Economic Law, 2021)
The purpose of this study is to find out how the Status of Virtual Gold Ownership in the Shopee Application is reviewed by DSN Fatwa No. 77/DSN-MUI/VI/2010 concerning the Sale and Purchase of Gold in Cashless Seen from the process of transferring ownership rights through buying and selling. This study uses a descriptive qualitative approach research method. The results of this study can be seen that; 1) Virtual gold ownership in the Shopee application in Islam is included in imperfect ownership because it is only a gold balance (intangible); 2) The process of ownership or transfer of virtual gold ownership rights through buying and selling in the Shopee application is considered invalid because the virtual gold ownership does not fulfill the muamalah contract, namely the absence of the handover of goods (Gold); 3) The status of virtual Gold ownership is reviewed by DSN MUI fatwa No. 75/DSN MUI/VII/2009 regarding buying and selling of non-cash Gold in the Shopee application is legal (Mubah). The ownership of virtual Gold purchased for cash is valid if there is a handover of goods/objects. However, there is no handover of goods in the Shopee application, so ownership is considered invalid.